2021
DOI: 10.1038/s41598-021-98210-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcriptome alterations in the prefrontal cortex, hippocampus, amygdala and hippocampus of suicide victims

Abstract: Suicide is one of the leading causes of death globally for all ages, and as such presents a very serious problem for clinicians worldwide. However, the underlying neurobiological pathology remains to a large extent unknown. In order to address this gap, we have carried out a genome-wide investigation of the gene expression in the amygdala, hippocampus, prefrontal cortex and thalamus in post-mortem brain samples obtained from 20 suicide completers and 7 control subjects. By KEGG enrichment analysis indicated we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 111 publications
(113 reference statements)
0
19
0
Order By: Relevance
“…Animal and human studies have shown that epigenetic mechanisms can regulate DNA transcription in response to environmental factors and may play a role in the pathological and physiological processes of depression [ 13 ]. Epigenetics refers to changes in expression level of a gene not involving changes in the DNA sequence, such as DNA methylation, histone modification, noncoding RNA, and chromatin remodeling [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal and human studies have shown that epigenetic mechanisms can regulate DNA transcription in response to environmental factors and may play a role in the pathological and physiological processes of depression [ 13 ]. Epigenetics refers to changes in expression level of a gene not involving changes in the DNA sequence, such as DNA methylation, histone modification, noncoding RNA, and chromatin remodeling [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the link between peripheral inflammation and SB ( Figure 1 ), conflicting changes in brain expression of cytokines such as TNF, IL1β, IL6, and IL10 were reported across post-mortem studies of individuals who died by suicide ( Supplementary Table 1 ; Torres-Platas et al, 2014b ; Clark et al, 2016 ; Schiavone et al, 2016 ; Wang et al, 2018 ; Snijders et al, 2020 ). Furthermore, according to gene ontology analysis, the DLPFC, AMY, and TLM of individuals with MDD who died by suicide can present lower expression of gene sets related to microglial immune functions such as “chemokine receptor binding” and “cellular response to LPS” compared to age- and sex-matched individuals with MDD deceased from other causes or healthy controls ( Pantazatos et al, 2017 ; Glavan et al, 2021 ). Such differences could be reconciled by the largely distinct brain regions studied, such as the VLPFC, ACC, and TLM, which likely present diverse baseline inter-individual immune activity, and therefore, a different susceptibility to peripheral inflammation ( Hodes et al, 2014 ; Wood et al, 2015 ).…”
Section: Suicidal Behaviors Are Associated With Increased Peripheral ...mentioning
confidence: 99%
“…A meta-analysis looking at 42 studies published between 1982 and 2019 found a statistically significant but weak influence of sleep disturbances on SB ( Harris et al, 2020 ). Despite the small effect, probably arising from inter-individual variability, lifestyle factors such as sleep are important elements to consider in the complex synergy of microglial features that convey susceptibility to psychiatric disorders ( Picard et al, 2021 ) and SB ( Glavan et al, 2021 ).…”
Section: Suicidal Behaviors Are Associated With Increased Peripheral ...mentioning
confidence: 99%
See 2 more Smart Citations